HOW QUALITY, SATISFACTION AND IMAGE CREATE LOYALTY AT AN INDONESIAN BANKING COMPANY: An Empirical Study in PT. Bank Bukopin, Tbk Malang Branch - Cunanda Ayu Oktiviane; Ananda Sabil Hussein (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to examine and explain how service quality, customer satisfaction and corporate image create customer loyalty in Indonesian banking company. The research was conducted in the area of Malang city, the individual customers who have  funding product owned PT. Bank Bukopin, Tbk in Malang city. Further  convenience sampling  technique  is used in this research with 150 people. The analysis tools are  Partial Least Square (PLS)  to determine the pattern and effect  relationships between variables in sequence, i.e. endogenous and exogenous variables. The  results of the study explained that there is a significant effect between  the  service quality to the customer satisfaction and corporate image,  the  corporate image to  the  customer satisfaction and  the  customer satisfaction to  the customer loyalty  Keywords: Service quality, customer satisfaction, corporate image, customer loyalty